Leptospiral infections in stray dogs in Malaysia - Abdul Mutalib, Abdul Rahim; Mohd Lila, Mohd Azmi; Bahaman, Abdul Rani; Phoumoona, T. (Veterinary Association Malaysia, 2009)
Leptospirosis is a zoonotic disease of worldwide importance. Besides rodents, dogs have also been implicated as a source of infection to humans. Samples of urine and blood from 142 stray dogs were examined for leptospirosis by serological tests and bacterial cultures. Of these, 83% (118/142) and 33% (471142) of the serum samples were positive by ELISA-IgM/IgG and the microscopic agglutination test (MAT) respectively. No leptospiral isolates were obtained on culture. Leptospira interrogans serovar pomona was found to be the most predominant serovar in the dogs with an infection rate of 68% at MAT titres of ~ 100. Urine and serum samples were randomly selected for detection and identification of leptospires by the polymerase chain reaction (PCR) and low-stringency PCR assay respectively. All seropositive samples selected were positive by PCR assay. One urine sample showed the presence of leptospires based on PCR assay.